RANCANG BANGUN APLIKASI PENGENALAN BATIK TULIS PASEBAN BERBASIS ANDROID - erik Kurniadi; Rika Nugraha (FKOM UNIKU, 2021)
There is a lot of useful information about batik culture, such as its history, the philosophical meaning of its motifs, to the development of the batik industry. However, knowledge about batik culture, especially in Paseban batik, is still poorly understood by the wider community, especially the Kuningan community itself. Based on the above background, the authors are interested in conducting research with the title